Sensitive Liquid Chromatographic Assay for Simultaneous Determination of Olmesartan and Its Prodrug Olmesartan Medoxomil in Rabbit Plasma - Sharma, T.; Moitra, S.K.; Gowrisankar, D.; Si, S.C. (Asian Journal of Chemistry, 2014)
A rapid, sensitive, precise and accurate reverse phase liquid chromatographic (RP-HPLC) method was developed and validated for olmesartan and its prodrug olmesartan medoxomil in rabbit plasma. The method was developed on symmetry C18 column (4.6 mm × 150 mm, 5 μm) using a mobile phase of acetonitrile: 0.1 % aqueous triethylamine adjusted to pH 6 with orthophosphoric acid (90:10 v/v). The peaks were eluted at 254 nm wavelength and no interferences found from plasma. The total run time was 10 min with a flow rate of 1 mL/min. Calibration plots were linear over the range of 2-100 ng/mL for olmesartan medoxomil and 0.5-20 ng/mL for olmesartan. Retention time of olmesartan medoxomil, olmesartan and internal standard (irbesartan) were 3.23, 4.85 and 6.90 min, respectively. The method has been successfully applied to pharmacokinetic studies of olmesartan medoxomil and olmesartan in rabbits. The results demonstrated that olmesartan medoxomil was rapidly and totally converted to its parent drug, olmesartan following oral administration. Olmesartan medoxomil is a prodrug of olmesartan.